Invención de una tradición: la fiesta de la independencia durante la construcción del Estado costarricense, 1821-1874 - Díaz Arias, David (Revista de historia., 2002)
This article analyzes the invention of Independence Day festivities in the civil calendar of the Costa Rican state, in the years 1821 to 1874, and reconsiders the function of civic celebrations in the construction of state and nation.